Self-organization and trade union democracy - Humphrey, Jill C. (2000)
This article is an offshoot of a three year study into the self-organized groups for women, black members, disabled members and lesbians and gay men which have been enshrined in the constitution of the UK's public sector union UNISON. The argument is that self-organization has become a significant axis around which trade union democracy is being reconstituted in the late twentieth century. However, our understanding of this phenomenon has been obscured by the ascendancy of mainstream union perspectives over self-organized perspectives, which has unfortunately been compounded by academic researchers. A re-conceptualization of self-organization proceeds in three stages. First, it is contextualized politically and theoretically in terms of trade union histories, new social movements and models of a diversified democratic polity. Second, it is re-signified by attending to its actual unfolding over the past two decades and the self-understandings of its activists. Third, is problematized with reference to exogenous pressures towards bureaucracy and oligarchy, and endogenous pressures towards essentialisms and exclusions. - Reproduced
Keywords: Trade unions; Self organizing systems; Labour relations